Methods used to estimate the poverty impact of increases in international food prices - Minot, Nicholas; Martin, Will (International Food Policy Research Institute, 2023)
The prices of agricultural commodities have increased on international markets since the outbreak of the Covid-19 pandemic in early 2020 and spiked after the invasion of Ukraine by Russia in February 2022. The price increases were particularly notable in the case of wheat, maize, and sorghum, which are staple foods in many developing countries. This prompted a wave of research to better understand the effect of these price changes on income and poverty in low-income countries. IFPRI carried out a set of country studies to explore the poverty impact of higher staple grain prices on six countries in sub-Saharan Africa: Mali, Burkina Faso, Niger, Nigeria, Kenya, and Ethiopia (see Martin and Minot, 2023a, 2023b, and 2023c and Minot and Martin, 2023a, 2023b, and 2023c). This brief describes the methods and data used in those studies.